Sedimentology of the Early Neogene Sarawak Basin (Onshore at Tatau Town to RumahSupitAkSeriang), Bintulu, Sarawak, Malaysia - Bin Mostaffa, Muhammad Iman (Universiti Teknologi PETRONAS, 2016)
This study focuses on the geology of the Neogene rocks of Sarawak Basin that overlies the unconformity on top of the Belaga Formation at Tatau Town to RumahSupitAkSeriang with the focal study on sedimentology to acquire a detailed analysis on the facies of the Tatau formation, and to evaluate the facies succession of the studied area as well as to re-construct a depositional environment of the Neogene succession in the Tatau area. Tatau formation is deposited from the sediments of the Belaga Formation during the Neogene age. A detailed framework of the depositional history of the study area is now possible with more exposed outcrops and hence will create better data collection and contribute to a better understanding on the geology of the Neogene rocks at Tatau Town to RumahSupitAkSeriang. There are generally eight facies observed in the field: (1) Coal; (2) Parallel laminated sandstone; (3) Cross-laminated sandstone; (4) Massive sandstone; (5) Heterolithic siltstone interbedded with cross-stratification sandstone; (6) Parallel laminated siltstone and sandstone; (7) Parallel laminated siltstone with climbing ripple sandstone; (8) Parallel laminated siltstone. The eight facies were described and interpreted in this research and concluded that the Neogene rocks of the Tatau town area are deposited at a transitional environment o